Stratification duration and the formation of bottom hypoxia over the Texas-Louisiana shelf. (5th June 2020) - Zhang, Wenxia; Hetland, Robert D.; Ruiz, Veronica; DiMarco, Steven F.; Wu, Hui
Abstract: Stratification has been proved to be essential to the development and sustainment of bottom hypoxia off the Texas-Louisiana shelf. Observations indicate that bottom hypoxia does not always arise under strong stratification, especially in spring/winter season when the strong stratification is transient. A simple oxygen model is coupled with a high-resolution hydrodynamic model to further investigate linkage between stratification and oxygen dynamics. We put forward a definition of stratification when vertical stratification maxima exceeds some critical value. This duration time is longest in summer and shortest in winter, and is identified regulating the horizontal and vertical extensions of bottom hypoxia. A long duration of strong stratification expands over the shelf, defining a stratification envelope within which bottom hypoxia occurs with high probability. Persistent strong stratification also acts to reserve local oxygen depletion, facilitating the growth of the hypoxic layer thickness. The main pycnocline is identified to be the upper limit of the top reach of bottom hypoxia. Highlights: Stratification duration is longest in summer and shortest in winter. The duration regulates the horizontal and vertical extents of bottom hypoxia. The main pycnocline is identified to be the upper limit of top reach of bottom hypoxia.